Unpacking the impact of social support on maternal mental health - Nyirenda, Tessa (My University, 2020)
The purpose of this research is to shed light on maternal mental health, specifically antenatal anxiety and depression. This was done because of the lack of awareness and support for mothers’ mental well-being during their pregnancy journey, especially for first time mothers. The research aimed to highlight these gaps by showing the real-life impact that these gaps have on mothers, through unpacking their narratives and experiences of pregnancy. Due to the sensitivity of such a study, it was very important to tread lightly and to be mindful of the mothers’ well-being throughout. This research investigated, at great length, the role healthcare professionals played in mothers’ pregnancy journeys and even more importantly how social support or a lack thereof was received by mothers. This study unpacked social support as an indicator of antenatal anxiety and depression, which has been under-researched. Support was at the epicentre of mothers’ narratives and told a story of antenatal anxiety and depression that has not nearly been researched enough. The use of the qualitative approach allowed for these narratives to be told and analysed in this study. This research unpacked the numerous gaps that arise due to a lack of supportive maternal mental healthcare, and identify the need for further mental healthcare assessments, and the unpacking of the severity of the structural violence experienced by mothers during pregnancy. This is important so as to understand the nature of the problem and so as to no longer subject mothers to such experiences
A research report submitted for the degree of Masters in Sociology in the Faculty of Humanities, University of the Witwatersrand, 2020